Analysis of the quality of electronic educational resource collections - Варава, Ірина; Гуралюк, Андрій; Шило, Олексій (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2025)
The article analyzes contemporary approaches to ensuring the quality of electronic educational resources (EERs) and digital collections in the context of digital transformation in education. The paper reveals that despite existing international standards (ISO/IEC 19796, ISO 27730:2012, NISO recommendations), they do not fully cover the specific pedagogical, methodological, and didactic requirements essential for the effective use of EERs in higher education. The rapid growth in the volume of digital materials does not guarantee their quality, and the lack of unified evaluation criteria complicates the selection, systematization, and integration of such resources into the educational process. The study substantiates the need to view an EER collection as a comprehensive system, the quality of which is determined by five key aspects: conceptual and objective clarity, structural organization, internal consistency, functional stability, and alignment with user needs. The five key system-forming components are discussed: conceptual clarity, organizational and structural quality, resource consistency and complementarity, functional sustainability and update mechanisms, and user orientation. The proposed approach emphasizes that a quality collection acts not merely as a repository but as a structured educational tool. Furthermore, the paper outlines 14 key criteria suitable for expert evaluation of virtual EER collection displays, including intuitiveness, accessibility, adaptability, visualization quality, interactivity, and search functionality. The proposed systemic approach creates a foundation for developing a model for the comprehensive assessment of EER collection quality, thereby enhancing the effectiveness of their utilization in higher education institutions.